Secagem em leito fixo de sementes com mucilagem - Prado, Manoel Marcelo do (2004)
Attempting to contribute with the studies on mucilaginous seeds drying, the objective of this work is to study the simultaneous heat and mass transfer during drying in fixed bed of papaya seeds with and without mucilage. The physical-mathematical analysis used to predict the moisture and temperature profiles during drying was based on two-phases model, according to mass and heat balances in fluid and particulate phases. A moving coordinate system, that follows the bed contraction movement, was used to take into account the shrinkage phenomenon. Experimental investigations in a drying unit at bench scale were conducted to characterize the phenomenon of shrinkage and the physical properties of material as function of moisture content, as well as to determine the temperature and moisture content distributions, which were used to evaluate the model. The equations of thermodynamics equilibrium and heat and moisture transfer rate between the solid and fluid phases were obtained from specific studies. The model equations were solved using the finite difference method. Although the beds of mucilaginous seeds had the higher heat transfer rates, their drying rates were lower than those of non-mucilaginous seeds. Bed shrinkage was nearly 30% and 12% for seeds with and without mucilage, respectively, what is directly related to superficial characteristics of each particle and moisture gradients developed during drying. The analysis of the fixed bed drying of papaya seeds, which was based on the two-phases model, corroborated the importance of the bed shrinkage for a more accurate interpretation of heat and mass phenomena involved in drying of particles with high moisture contents. It is verified that the developed model is promising to predict the drying variable and that it must be tested in correlated studies.